Investigation into clinicopathological and pathological findings, prognosis, and aetiology of lorikeet paralysis syndrome in rainbow lorikeets (Trichoglossus haematodus). Issue 10 (13th July 2021) - Lacasse, C; Rose, K; Allen, M; Ward, MP; Pulscher, LA; Giles, A; Hall, J; Phalen, DN
Abstract : Objective: To report the temporal and spatial distribution of rainbow lorikeets presenting with lorikeet paralysis syndrome (LPS) and their clinicopathologic and pathologic findings, exposure to toxins, and response to treatment. Methods: Records of lorikeets admitted in 2017 and 2018 to facilities in south‐east Queensland (QLD) were reviewed and LPS and non‐LPS cases were mapped and their distribution compared. Plasma biochemistries and complete blood counts were done on 20 representative lorikeets from south‐east QLD and Grafton, New South Wales (NSW). Tissues from 28 lorikeets were examined histologically. Samples were tested for pesticides (n = 19), toxic elements (n = 23), botulism (n = 15) and alcohol (n = 5). Results: LPS occurred in warmer months. Affected lorikeets were found across south‐east QLD. Hotspots were identified in Brisbane and the Sunshine Coast. Lorikeets had a heterophilic leucocytosis, elevated muscle enzymes, uric acid and sodium and chloride. Specific lesions were not found. Exposure to cadmium was common in LPS and non‐LPS lorikeets. Treated lorikeets had a 60–93% See Table 2 depending on severity of signs. Clinical significance: The primary differential diagnosis for lorikeets presenting with lower motor neuron signs during spring, summer and autumn in northern NSW and south‐east Queensland should be LPS. With supportive care, prognosis is fair to good.